Embedding local cultural richness in English language education: a place-based dual-core approach for rural schools in China - Shi, Hong; Ma, Lirui (Frontiers in Education, 2025)
This study examines the implementation of place-based education in rural English teaching in China through a mixed-methods approach, encompassing surveys and interviews with rural middle school students and teachers. The findings reveal significant challenges, including the disconnection between English education and local culture, the limited integration of local knowledge into textbooks, and the absence of localized professional development for educators, etc. Both students and teachers report insufficient incorporation of local cultural elements into English classes, which adversely affects learning engagement and cultural identity formation. To address these issues, the study proposes a “Dual-Core” approach. The first core focuses on establishing an educational team that prioritizes optimizing decision-making processes, integrating resources, and refining evaluation systems. The second core emphasizes enhancing teachers’ and students’ awareness of local culture through targeted beliefs training, preparation training, and curriculum training. These measures aim to enhance teaching effectiveness, strengthen students’ connection to their communities, and contribute to rural revitalization efforts. This research provides actionable recommendations for advancing English education in rural areas, promoting educational equity, and fostering cultural sustainability.